Hakikat Kematian dalam Al-Qur’an - Badi'ati, Alfi Qonita (SHAHIH: Journal of Islamicate Multidisciplinary, 2020)
Death is an absolute necessity for every living creature. Belief in death and post-mortal life is certainly very influential on the quality of one's life. As well as understanding the meaning of martyrdom for certain groups. This understanding has an impact on the lives of other groups, such as suicide bombings, attacking other groups deemed heretical. In addition, various beliefs (religion) also interpret death and life afterwards with various interpretations. The focus of this study is the interpretation of the verse of death in the Qur'an. The method used is the interpretation maudhuâ€™i. Based on this method, the discussion of the problem of death will be increasingly focused. The findings of the data regarding death in the Qur'an are represented by the words Ù…Ø§Øª, ÙˆÙÙ‰, and Ø§Ù…Ø³Ùƒ following the following derivatives. From this sentence we get the subject of death in the Qur'an as a whole. Among them are discussions about the inevitability of death for every soul that lives, about the process of death, doubts about post-mortal life, and charity replies that will be downloaded after being resurrected.